1999
DOI: 10.1210/en.140.7.3219
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor- -Activated Cell Death Pathways in NIT-1 Insulinoma Cells and Primary Pancreatic   Cells

Abstract: Tumor necrosis factor-alpha (TNFalpha) is a potential mediator of beta cell destruction in insulin-dependent diabetes mellitus. We have studied TNF-responsive pathways leading to apoptosis in beta cells. Primary beta cells express low levels of the type I TNF receptor (TNFR1) but do not express the type 2 receptor (TNFR2). Evidence for TNFR1 expression on beta cells came from flow cytometry using monoclonal antibodies specific for TNFR1 and TNFR2 and from RT-PCR of beta cell RNA. NIT-1 insulinoma cells similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 0 publications
4
53
0
Order By: Relevance
“…However, the in vivo role of the cytokine in diabetes development has not yet been fully elucidated. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Our IFN-␥/TNF-␣ synergism model nicely explains why transgenic expression of TNF-␣ alone could not induce diabetes in some of the previous studies in which pancreatic expression of TNF-␣ alone did not accelerate diabetes development (21).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the in vivo role of the cytokine in diabetes development has not yet been fully elucidated. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Our IFN-␥/TNF-␣ synergism model nicely explains why transgenic expression of TNF-␣ alone could not induce diabetes in some of the previous studies in which pancreatic expression of TNF-␣ alone did not accelerate diabetes development (21).…”
Section: Discussionsupporting
confidence: 55%
“…The role of TNF-␣ as an effector has been extremely ambiguous. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Neonatal islet-specific expression of TNF-␣ promoted diabetes by enhancing the presentation of islet Ags (16,17).…”
mentioning
confidence: 98%
“…34 It is of note that primary b pancreatic cells and insulinoma cells have been shown to express low levels of the p55 receptor but not the p75 receptor. 31 The potential cytotoxic effects of TNFa on HIT-T15 cells has not been examined in our study. This possibility seems unlikely, however, given that the cytotoxic effects of TNFa on b-cells apparently require higher concentrations of TNFa, 35 or the simultaneous presence of other cytokines such as IFN-g andaor IL-1b, 36 ± 38 which was not the case in our system.…”
Section: Inhibition Of Insulin Transcription By Tnfa and Leptinmentioning
confidence: 93%
“…6 ± 8 TNFa activity has been shown to exist in pancreatic islets and in insulinoma cells. 30,31 Thus, the mechanism of TNFa-mediated insulin resistance that exist in peripheral tissues, could also be expected to operate on pancreatic b-cells and in¯uence their function, as they also express insulin receptors that are required for normal glucose-stimulated insulin secretion. 5 Interestingly, it was demonstrated that insulin receptor signaling also appears to in¯uence insulin gene expression and insulin content in the b-cell.…”
Section: Inhibition Of Insulin Transcription By Tnfa and Leptinmentioning
confidence: 99%
“…Defining the signalling components of apoptosis present in beta cells is important because it could provide insights into potential pathogenic mechanisms and might lead to the development of pharmacological interventions for the treatment of Type I diabetes. Several apoptosis signalling pathways, initiated by death receptor ligands such as Fas ligand (FasL) and TNF-α have been shown to be active in mouse islet beta cells and could be involved in destructive insulitis [4,5,6,7]. TRAIL (also known as Apo2 ligand) is a 40-kDa type II transmembrane protein that is structurally related to the TNF family of proteins including TNF-α and FasL [8,9].…”
mentioning
confidence: 99%